2022
DOI: 10.3390/su14031071
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 on the Fisheries and Aquaculture Sector in Developing Countries and Ways Forward

Abstract: Fish is a major source of food and nutritional security for subsistence communities in developing countries, it also has linkages with the economic and supply-chain dimensions of these countries. Burgeoning literature has revealed the adverse impacts of COVID-19 on the fisheries and aquaculture sector, which serves as the major source of income and employment for numerous people globally. This study has employed a systematic literature review of the overall impacts of COVID-19 on the fisheries and aquaculture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 49 publications
(77 reference statements)
0
27
0
1
Order By: Relevance
“…The damage to the aquaculture sector in China caused by COVID-19 has been reported to be far-reaching due to input, production, marketing, and export problems [24]. It has been reported that COVID-19 has adverse impacts on aquaculture production in a number of Asian countries, including Bangladesh, Cambodia, India, Indonesia, Laos, Myanmar, the Philippines, Thailand, and Vietnam [21,[25][26][27]. In Malaysia, aquaculture production has been affected by the pandemic due to transport disruption, interruption of supply chains, reduction in feed supply, and reduction in seafood demand [20,28].…”
Section: Aquaculture Practices In the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…The damage to the aquaculture sector in China caused by COVID-19 has been reported to be far-reaching due to input, production, marketing, and export problems [24]. It has been reported that COVID-19 has adverse impacts on aquaculture production in a number of Asian countries, including Bangladesh, Cambodia, India, Indonesia, Laos, Myanmar, the Philippines, Thailand, and Vietnam [21,[25][26][27]. In Malaysia, aquaculture production has been affected by the pandemic due to transport disruption, interruption of supply chains, reduction in feed supply, and reduction in seafood demand [20,28].…”
Section: Aquaculture Practices In the Covid-19 Pandemicmentioning
confidence: 99%
“…There is great cause of concern about the impact of COVID-19 pandemic on input supply of various aquaculture practices. Because of inadequate and/or irregular input supply, COVID-19 affects aquaculture in several Asian countries, including Bangladesh, China, India, Indonesia, Myanmar, the Philippines, Thailand, and Vietnam [21,27]. There are concerns of aquaculture practices by limiting input supply, which undermine fish production (Fig.…”
Section: Input Supply Disruptionmentioning
confidence: 99%
“…Consumer demand is growing across the fish value chains, and some fish stocks are becoming less sustainable (Pradeepkiran, 2019). It takes a complicated set of actions to get fish and fish products from fisheries and aquaculture production to final customers and the methods used to handle these value chains range from artisanal to highly industrial (Alam et al, 2022). The important steps in a supply chain for fisheries or aquaculture product include fishing, aquaculture production, processing, input transit, distribution, wholesale marketing and retail marketing.…”
Section: Why Fisheries and Aquaculture Food Systems Were Vulnerable T...mentioning
confidence: 99%
“…For instance, due to the significant drop in the market's demand for fish and the limited transportation options that were available during the lockdown, fish farms have had difficulty in collecting and selling their goods (FAO, 2021). As farmers were unable to sell their products there was an increase in live fish stock levels and a lengthening of the fish culture period, both of which negatively impacted the feed conversion ratios, the ability to restock and, ultimately, the farms' profitability (Alam et al, 2022). Accordingly, the risky of fish mortality and feeding expenditures grew (Fiorella et al, 2021;Alam et al, 2022).…”
Section: Impacts Of Covid-19 On Aquaculture Sector In Kenyamentioning
confidence: 99%
See 1 more Smart Citation